Neurotrophic Effect of Fish-Lecithin Based Nanoliposomes on Cortical Neurons - Catherine Malaplate; Aurelia Poerio; Marion Huguet; Claire Soligot; Elodie Passeri; Cyril J. F. Kahn; Michel Linder; Elmira Arab-Tehrany; Frances T. Yen (Marine Drugs, 2019)
Lipids play multiple roles in preserving neuronal function and synaptic plasticity, and polyunsaturated fatty acids (PUFAs) have been of particular interest in optimizing synaptic membrane organization and function. We developed a green-based methodology to prepare nanoliposomes (NL) from lecithin that was extracted from fish head by-products. These NL range between 100−120 nm in diameter, with an n-3/n-6 fatty acid ratio of 8.88. The high content of n-3 PUFA (46.3% of total fatty acid content) and docosahexanoic acid (26%) in these NL represented a means for enrichment of neuronal membranes that are potentially beneficial for neuronal growth and synaptogenesis. To test this, the primary cultures of rat embryo cortical neurons were incubated with NL on day 3 post-culture for 24 h, followed by immunoblots or immunofluorescence to evaluate the NL effects on synaptogenesis, axonal growth, and dendrite formation. The results revealed that NL-treated cells displayed a level of neurite outgrowth and arborization on day 4 that was similar to those of untreated cells on day 5 and 6, suggesting accelerated synapse formation and neuronal development in the presence of NL. We propose that fish-derived NL, by virtue of their n-3 PUFA profile and neurotrophic effects, represent a new innovative bioactive vector for developing preventive or curative treatments for neurodegenerative diseases.